Analysis Of Functional Indicators Of Physical Training Of Young Athletes In Taekwondo - Nozima Xolmuxammedova (Zien Journals, 2025)
This article examines the analysis of functional indicators of physical fitness in young taekwondo athletes, as well as methods for their assessment. The study aims to identify changes in athletes' physical fitness as a result of implementing an experimental training program. The results show that targeted training positively affects key indicators such as cardiovascular endurance, strength, and aerobic power.
Keywords: taekwondo; physical fitness; young athletes